RADIATIVE TRANSFER EFFECTS ON THE COLORS OF RR LYRAE STARS - Davis, C. G. (Одеські астрономічні публікації, 2017)
The methods of Davis and Cox (1980), are applied to a series of models described by Bono and Stellingwerf (1994) to deter-mine the colors of RR Lyrae stars. Convection is ignored and the radiation flow is treated by a complete variable Eddington, multi-frequency dependent radiative transfer approximation.